Pengaruh Kualitas Produk dan Kualitas Pelayanan Terhadap Kepuasan Pelanggan Indihome di Toraja Utara Periode 2023-2024 - Desi Desi; Helba Rundupadang; Mince Batara (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
The aim of this research is to find out how product quality affects customer satisfaction, to find out whether service quality has an effect on customer satisfaction, and to find out whether product quality and service quality influence on indihome customer satisfaction in North Toraja. The type of research used in this research is quantitative with data collection using questionnaires and documentation. The results of this research indicate that product quality has no influence on Indihome customer satisfaction in North Toraja with a Tcount value of -1.324 < Ttable of 1.986 and a significant value of 0.189 > 0.025, Service Quality has an influence on Indihome customer satisfaction in North Toraja with a Tcount value of 7,803 > T table of 1,986. Product quality has no effect on customer satisfaction with a significant value of 0.189 > 0.025 and a T value of -1.324 < T table 1.986. Meanwhile, service quality has an influence on customer satisfaction with a significant value of 0.000 > 0.025 and a T value of 7.803 > 1.986